‘Sho-Goh-Wah-Pee-Nay’ - The sugar disease: Not so sweet! - Mundra, Vishal (Journal of Social Health and Diabetes, 2013)
“Sho-goh-wah-pee-nay” or “sugar disease,” an Oji-Cree word (Native American Indian terminology), is more commonly known as “diabetes." Over the last 70 years, diabetes has become an epidemic within Native American Indian tribes. At about 16%, American Indians and Alaska Natives have the highest occurrence of diabetes in the United States. There are 566 federally recognized tribes. Drifting genes, obesity, and lower educational levels are among the well-known causes of disease management in this group. However, often forgotten are the socio-cultural aspects of this issue. Disease perception, diet, traditional medicine, poor communication, sedentary lifestyle, poor socio-economic status are most important obstacles. Various government-funded programs like National Diabetes Education Program, “We have the power to prevent diabetes” and “Move it! And reduce your risk of diabetes” and diabetes prevention program are in place. Similar guidelines should be developed for all the ethnic or tribal groups across the world before it becomes a pandemic.
Keywords: American Indian and Alaskan Indian; diabetes; government programs; social and cultural barriers